2006
DOI: 10.1063/1.2216694
|View full text |Cite
|
Sign up to set email alerts
|

Surface-enhanced Raman scattering of silver-gold bimetallic nanostructures with hollow interiors

Abstract: Surface-enhanced Raman scattering (SERS) activity of silver-gold bimetallic nanostructures (a mean diameter of ∼100nm) with hollow interiors was checked using p-aminothiophenol (p-ATP) as a probe molecule at both visible light (514.5nm) and near-infrared (1064nm) excitation. Evident Raman peaks of p-ATP were clearly observed, indicating the enhancement Raman scattering activity of the hollow nanostructure to p-ATP. The enhancement factors (EF) at the hollow nanostructures were obtained to be as large as (0.8±0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 54 publications
2
37
0
Order By: Relevance
“…Au/Ag plasmon shifts have also been studied in a variety of other morphologies and applications. Studies of the surface-enhanced Raman scattering of Au/Ag hollow nanostructures [31], hyper-Raleigh scattering of Au core, Ag shell particles [32], and other spectroscopic techniques have been examined, as well as direct imaging of the nanoparticles [33].…”
Section: Influence Of Bimetallic Nanoparticles On Improving Plasmonicmentioning
confidence: 99%
“…Au/Ag plasmon shifts have also been studied in a variety of other morphologies and applications. Studies of the surface-enhanced Raman scattering of Au/Ag hollow nanostructures [31], hyper-Raleigh scattering of Au core, Ag shell particles [32], and other spectroscopic techniques have been examined, as well as direct imaging of the nanoparticles [33].…”
Section: Influence Of Bimetallic Nanoparticles On Improving Plasmonicmentioning
confidence: 99%
“…On the other hand, Tian et al [57] have carried out excellent work to generate SERS directly on transition metals (e.g., Pt, Ru, Rh, Pd, Fe, Co, Ni, and their alloys) by developing various roughening procedures and optimizing the performance of the confocal Raman microscope. More recently, functional nanocolloids, such as mixed silver/gold colloids [58] and hollow gold nanospheres (HGNS) [59][60][61], have been introduced. Silver-coated gold colloids can be prepared by growing the seeds of silver nanoparticles on gold surfaces by chemical reduction methods.…”
Section: Preparation Of Metal Nanocolloids and Their Characterizationmentioning
confidence: 99%
“…Similar research was done by Rivas et al, who prepared Ag-coated Au and Au-coated Ag colloidal particles through chemical reaction and found that the composition of Ag/Au colloidal particles depends on the relative amount of the depositing metal; the SERS activity of the bimetallic nanoparticles was found to be placed between that of Ag and Au particles [103]. Silver/gold bimetallic nanoparticles with hollow interiors were made by our group and these showed great enhancement for the probe molecules [106]. Composite Au/Ag or Ag/Au core-shell nanoparticles were also fabricated for SERS substrate [107,108] and used for single-molecule detection [100].…”
Section: Bimetallic Nanoparticle Sers Substratementioning
confidence: 99%